THE UTILIZATION OF STRUCTURAL EQUATION MODELLING TO DETERMINE CASUALITY ON CONSUMER DECISION OF E-WALLET - Hartati, Hartati; Saluza, Imelda; Iisnawati, Iisnawati; Teguh, Teguh (PATTIMURA UNIVERSITY, 2024)
One of the technological innovations that exemplifies transactional innovation is the use of an E-Wallet as a means of carrying out financial transactions. This invention enhances transactional ease and quickness. The E-Wallet is the most popular means of financial transaction among the general population. The traditional marketing mix has developed into the product, price, place, promotion, personalization, privacy, customer service, community, site, security, and sales promotion (4Ps+P2C2S3). These criteria are used to evaluate their efficacy in persuading customers to adopt an E-Wallet. Structural Equation Modeling (SEM) is used to assess the causal link between e-marketing mix items and customer decisions to use E-Wallet. SEM provides the core capability of validating the validity and reliability of procedures such as Confirmatory Factor Analysis (CFA). by investigating the pattern of linkages between latent variables and showing them with route diagrams. This study employed 200 E-Wallet users in Palembang for modeling. with the criterion of having one of the E-Wallet programs on a smartphone and having used the application at least once. According to the results of the consumer response processing. all constructs have Cronbach's Alpha (CA) > 0.60, indicating that all constructs are valid for use in measurement. As do the Average Variance Extracted (AVE) and Composite Reliability (CR) values > 0.70, indicating that the construct explains more than half of the variance coming from the indicators. Furthermore, we show the results of evaluating the causal relationship between endogenous construct elements that influence customer decisions, such as location, security, and sales promotion.